Alat Penangkapan Ikan Yang Ramah Lingkungan Berbasis Code of Conduct For Responsible Fisheries di Kota Banda Aceh - Zainal Sumardi; M. Ali Sarong; Muhammad Nasir (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
ABSTRACT. This study aims to (1) know the fishing gear that has the highest level of environmental friendliness (2) aspects of the code of conduct for responsible fisheries CCRF is often violated and (3) determine the level of concern for fishermen to use fish-friendly tool arrests lingkungannelaya Banda Aceh. The study was conducted in March through May 2014 in Fishing Port Beach (PPP) Lampulo and Fish Landing Places (TPI) Alue Naga. Descriptive method with the number of samples used in this study divided 175 people fishing the Purse Seine fishing, Tramell Net, and Gill Net Fishermen. Collecting data using a questionnaire and analysed using descriptive analysis of the results of the research described in graphic form, frequency and percentage (persen). The results of the study (1) a means of catching the highest level of environmental friendliness is a gill net (2) Aspects of CCRF most often violated by fishermen is the aspect of fishing gear selectivity and fishing aspects of the Act are protected and (3) the highest awareness level of fishing gears environmentally friendly fishing is done by using the capture tool Gill Net.